IMPACT OF GREEN ACCOUNTING, MATERIAL FLOW COST ACCOUNTING, CAPITAL STRUCTURE ON FINANCIAL PERFORMANCE WITH FIRM DEBT AS MODERATOR - Wulandari, Wulandari; Mukhzarudfa, Mukhzarudfa; Dica Lady Silvera, Dica Lady Silvera (Journal of Applied Finance and Accounting, 2025)
This study examines the effect of green accounting, material flow cost accounting (MFCA), and capital structure on financial performance, with firm debt as a moderating variable. Using a quantitative approach, the research analyses secondary data from 109 basic materials sector companies listed on the Indonesia Stock Exchange (IDX) for the 2016–2023 period. Data were collected through documentation and analysed using Microsoft Excel and E-Views 12 with panel data regression, including model selection tests, classical assumption tests, and descriptive statistics. T-tests and the coefficient of determination (R²) were employed to assess the significance of each variable. The findings show that green accounting significantly affects financial performance, while MFCA and capital structure do not. Firm debt moderates the relationship between green accounting and financial performance but has no moderating effect on the influence of MFCA and capital structure. Theoretical implications support the view that environmental sustainability, represented by green accounting, contributes to firm value, aligning with stakeholder and legitimacy theories. Companies are encouraged to adopt green accounting as a strategic tool, particularly in environmentally intensive industries, and to consider debt structure to maximise its financial impact. Future research should investigate other sectors or external factors influencing the effectiveness of MFCA and capital structure. Broader samples and mixed methods may also enhance understanding of how environmental and financial strategies interact in corporate settings.